Pendampingan Pembelajaran Kosa Kata Bahasa Inggris dan Bahasa Indonesia di Miracle Language Center, Narathiwat, Thailand - Ayu; Sulistyowati (LPPM Universitas Timor, 2025)
The purpose of assisting this vocabulary learning is to increase the Foreign Language Skills of Elementary School-Age Children at the Miracle Language Center. Method This research uses community education methods to provide assistance in English and Indonesian vocabulary. The location of vocabulary learning assistance was carried out at the Miracle Language Center, Narathiwat, Thailand which was carried out for 3 weeks, starting from August 15, 2023, to September 5, 2023. This activity was held at the Miracle Language Center, located in Narathiwat, Thailand held on Monday - Friday at 09.15-10.15.00 WIB. The results of this mentoring activity include several things, such as increasing motivation in learning foreign languages, and progress in vocabulary mastery through the vocabulary provided.